Experimental Studies on n-Octane and Cyclohexane as Organic Solvent for Synthesis of Polyurea Microcapsules by Interfacial Polycondensation - Christian, Ujvala P.; Wagh, Shrikant J. (Asian Journal of Engineering and Applied Technology, 2018)
Interfacial polycondensation (IP) is one of the most important step polymerization technique used for synthesis of polyurea microcapsules. IP reaction between diamine and diisocyanate monomers which are soluble in aqueous phase and organic phase respectively is very fast therefore the overall process of polyurea synthesis via interfacial polycondensation, by and large, mass transfer controlled reaction. Selection of proper organic solvent is one of the important parameter for IP reactions. The objective of this experimental work was to study the effect of n-Octane and Cyclohexane as an organic solvent on kinetics of polyurea microcapsules synthesized by interfacial polycondensation reaction. In this reaction system IP reaction occurs on organic side of the interface so reaction rate increased with increase in relative polarity of organic solvent. Characterization of polyurea was carried out by XRD and DSC which demonstrated that semi crystalline polyurea microcapsules with good thermal stability were synthesized.